2010
DOI: 10.3109/02656730903272917
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of diabetic mice treated with whole body hyperthermia: A high-density DNA microarray analysis

Abstract: Previously we have demonstrated that whole body hyperthermia (WBH) improves insulin resistance in diabetic mice. The aim of the present study was to perform a gene expression analysis of the liver and adipose tissue of obesity-induced insulin resistant diabetic mice (db/db mice) after WBH and to define the molecules that play the important role in improvement of insulin resistance by WBH. Male db/db mice were treated with WBH 3 times per week for 12 weeks. Total RNA was extracted from the liver and adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…Similarly, diabetic rats have an increased mortality rate when exposed to severe heat, and exogenous insulin increases their survival time (Niu et al, 2003). Furthermore, nonlethal heat stress ameliorates proxies of insulin insensitivity in diabetic rodents (Kokura et al, 2007(Kokura et al, , 2010 or rodents fed high fat diets (Gupte et al, 2009). This is similar to reports indicating that thermal therapy (e.g., saunas and hot baths) improves insulin sensitivity in humans (McCarty et al, 2009).…”
Section: Insulinsupporting
confidence: 74%
“…Similarly, diabetic rats have an increased mortality rate when exposed to severe heat, and exogenous insulin increases their survival time (Niu et al, 2003). Furthermore, nonlethal heat stress ameliorates proxies of insulin insensitivity in diabetic rodents (Kokura et al, 2007(Kokura et al, , 2010 or rodents fed high fat diets (Gupte et al, 2009). This is similar to reports indicating that thermal therapy (e.g., saunas and hot baths) improves insulin sensitivity in humans (McCarty et al, 2009).…”
Section: Insulinsupporting
confidence: 74%
“…Similarly, diabetic rats have an increased mortality rate when exposed to severe heat, and exogenous insulin increases their survival time (142). Furthermore, nonlethal heat stress ameliorates proxies of insulin insensitivity in diabetic rodents (143,144) or rodents fed high-fat diets (145). This is similar to reports indicating that thermal therapy (saunas and hot baths) improves insulin sensitivity in humans (146).…”
Section: Systemic Heat Stress Responsesupporting
confidence: 67%
“…(2009) reported that thermal therapy can improve insulin sensitivity in humans. Moreover, HS can ameliorate biomarkers of insulin sensitivity in diabetic rats ( Kokura et al., 2010 ) and rats fed a high-fat diet ( Gupte et al., 2009 ). Increased insulin sensitivity may be an essential component of the acclimation mechanism in HS.…”
Section: Discussionmentioning
confidence: 99%